Design an Automatic Transfer Switch for Solar Power Plant - Adi Pratama Putra; Adi Mulyadi (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
This paper discusses the automatic transfer switch (ATS) in solar power plants. ATS is used to transfer the main electrical power to a backup power source (battery). PLN power cannot supply electricity continuously due to non-standard ATS installations, blackouts, disturbances to the generating system, and distribution system. Two ATS systems are proposed to control the switching process of PLN and PLTS automatically using inverter standby mode (ISM) and inverter off mode (IOM). The results of the application of ISM to PLN and PLTS can supply power needs based on switching techniques to avoid equipment damage. While IOM can save battery for inverter power supply.